Initial experience in Brazil with the Helex septal occluder for percutaneous occlusion of atrial septal defects - Pedra,Carlos A.C. (2003)
OBJECTIVE: To evaluate the initial clinical experience with the Helex septal occluder for percutaneous closure of atrial septal defects. METHODS: Ten patients underwent the procedure, 7 patients with ostium secundum atrial septal defects (ASD) with hemodynamic repercussions and 3 patients with pervious foramen ovale (PFO) and a history of stroke. Mean age was 33.8 years and mean weight was 55.4 kg. Mean diameter by transesophageal echocardiography and mean stretched ASD diameter were 11.33 ± 3.3mm, and 15.2 ± 3.8mm, respectively. The Qp/Qs ratio was 1.9 ± 0.3 in patients with ASD. RESULTS: Eleven occluders were placed because a patient with 2 holes needed 2 devices. It was necessary to retrieve and replace 4 devices in 3 patients. We observed immediate residual shunt (< 2mm) in 4 patients with ASD, and in those with patent foramen ovale total occlusion of the defect occurred. No complications were noted, and all patients were discharged on the following day. After 1 month, 2 patients with ASD experienced trivial residual shunts (1mm). In 1 patient, we observed mild prolapse in the proximal disk in the right atrium, without consequences. CONCLUSION: The Helex septal occluder was safe and effective for occluding small to moderate atrial septal defects. Because the implantation technique is demanding, it requires specific training of the operator. Even so, small technical failures may occur in the beginning of the learning curve, but they do not involve patient safety.